Perception of teachers and students about the impact of the open library in schools in the north of Cajamarca - Cajandilay Díaz, Eduardo (2025)
Objective: To know the teachers and students perception about the impact of the implementation of their open Library had. Method: the research is biographical, it used the testimony as a technique to collect information. Through the researcher’s convenience criteria, 10 informers were selected who provided their testimony about their experiences. Results: the inferential analysis of the testimonies allowed us to establish three emerging categories in relation to the reading space: (1) expectancy in the educational community, (2) freedom to read the freely chosen texts, (3) improve the students’ learning process. Conclusions: the pleasure for reading is generated by the students’ interest and the opportunity to put them in direct contact with the texts. It is essential to reorganize libraries and generate many diferent reading spaces motivated by a dynamic model teacher whose reading experience motivates the pleasure for reading. Productive experiences must be replicated, disseminated and create the conditions for a reading culture.